Lempeng Desidua pada Kecurigaan Kehamilan Ektopik : Sebuah Laporan Kasus - Subuh, David Justin; Sitorus, Esther Reny Deswani (Universitas HKBP Nommensen, 2023)
Background: The decidual cast represents a condition which the entire endometrial lining is shed in intact condition through the vagina. This phenomenon is infrequent and has been linked to various factors, including ectopic pregnancy and the use of exogenous progesterone. In the current report, we present a case finding of ectopic pregnancy upon discovery of decidual cast.Case: Female, 36 years old, came with complaints of pain in the pelvic area accompanied by patches of bleeding from the genitals since 1 week ago. On the 8th day since the complaint was felt, the patient complained of severe pain accompanied by discharge of tissue from the genitals. On histopathological examination of the tissue, a decidual cast was found in the absence of chorionic villi. The pregnancy test was positive and on ultrasound examination we found a mass with a cavity measuring 1.55 x 1.53 cm in the left fallopian tube so that the diagnosis of tubal ectopic pregnancy was established and a laparoscopic procedure was carried out. Discussion: The decidual cast is a proliferation of the endometrial lining that is released through the vagina in an intact form. This finding of decidual cast is often found in ectopic pregnancies and is associated with exposure to exogenous progesterone. The release of the decidual cast through the undilated cervix will cause severe pain referred to as membranous dysmenorrhea. The differential diagnosis of this decidual cast finding is the occurrence of abortion. However, the results of histopathological examination of the tissue obtained a decidual cast without chorionic villi so that the possibility of abortion can be removed.Conclusion: The identification of a decidual cast is frequently linked to the occurrence of an ectopic pregnancy. Therefore, its presence should alert clinicians to consider the possibility of an ectopic pregnancy and conduct further investigations.